Contributions of different fractions of extracellular polymeric substances from waste-activated sludge to Cu(II) biosorption. Issue 45 (25th September 2016) - Miao, Lingzhan; Wang, Chao; Hou, Jun; Wang, Peifang; Ao, Yanhui; Li, Yi; Lv, Bowen; Xu, Yi; You, Guoxiang
Abstract: The extracellular polymeric substances (EPS) extracted from waste-activated sludge (WAS) were used as a novel biosorbent. The goal of this study was to quantify the contribution of EPS to copper immobilization by WAS. Through comparison of copper sorption using sludge with tightly bound EPS (TB-EPS) and sludge with minimal EPS, we demonstrated that TB-EPS from WAS contributed significantly to copper sorption, especially at low initial Cu 2+ concentrations. EPS probably became pseudo-saturated in terms of binding sites for copper sorption at high Cu 2+ concentrations; thus, cells may play a more dominant role. To quantify the relative contributions of copper sorption by EPS fractions, loosely bound EPS (LB-EPS) and TB-EPS were isolated from WAS and used in batch biosorption experiments. The results showed that TB-EPS exhibited a higher sorption capacity than LB-EPS in any pH solution applied in this study (3–6.5), due to a higher amount of functional groups (carboxylic groups) of TB-EPS. Scanning electron microscopy observation revealed that TB-EPS had a rough surface with long chains, making it more available for copper binding. Fourier transform infrared analysis further confirmed that the functional groups responsible for Cu 2+ biosorption primarily consisted of hydroxyl (–OH), carboxyl (–COOH), and amide (N–H). The functional groups with weaker affinity in EPS may play a more significant role in copper removal from the aqueous phase at high copper concentrations.